Patient-reported outcomes in patients with overactive bladder treated with mirabegron and tolterodine in a prospective, double-blind, randomized, two-period crossover, multicenter study (PREFER) - Sender Herschorn; David Staskin; Le Mai Tu; Jonathan Fialkov; Terry Walsh; Katherine Gooch; Carol R. Schermer (Health and Quality of Life Outcomes, 2018)
Abstract Background The PREFER study was an assessment of medication tolerability, treatment preference and symptom improvement during treatment with mirabegron (M) and tolterodine (T) extended release (ER) in patients with overactive bladder (OAB). In this analysis of PREFER, patient-reported outcomes (PROs) were assessed during treatment. Methods PREFER was a two-period, 8-week crossover, double-blind, phase IV study (NCT02138747) of treatment-naïve adults with OAB ≥3 months randomized to 1 of 4 treatment sequences (M/T; T/M; M/M; T/T), separated by a 2-week washout. Tolterodine ER was dosed at 4 mg for 8 weeks and mirabegron was dosed at 25 mg for 4 weeks then increased to 50 mg for the next 4 weeks. At each visit, PROs related to treatment satisfaction, quality of life and symptom bother were assessed using the OAB Satisfaction (OAB-S; 3 independent scales/5 single-item overall assessments), OAB-q (total health-related QoL [HRQoL] and subscales [Sleep, Social, Coping, Concern] and Symptom Bother scale) and Patient Perception of Bladder Condition (PPBC) questionnaires. Responder rates were reported for OAB-q subscales based on a minimal important difference (MID; ≥ 10-point improvement) and OAB-S Medication Tolerability score ≥ 90. Results In total, 358 randomized patients received ≥1 dose of double-blind study medication and completed ≥1 post-baseline value (OAB-S scale, OAB-q, PPBC): M/T (n = 154), T/M (n = 144), M/M (n = 30) or T/T (n = 30). At end of treatment (EoT), mirabegron and tolterodine ER were associated with similar mean improvements in 7 of the 8 OAB-S scores investigated, OAB-q scales and PPBC. A higher percentage of patients achieved clinically relevant improvements (MID) in OAB-q scales and OAB-S Medication Tolerability score during treatment with mirabegron than tolterodine ER. Conclusions On average, patients with OAB experienced improvements in treatment satisfaction, HRQoL and symptom bother that were of a similar magnitude during treatment with mirabegron or tolterodine ER. However, during mirabegron treatment, patients were more likely to achieve clinically relevant improvements in tolerability and HRQoL (as measured by the MID for the OAB-q or an OAB-S Medication Tolerability score ≥ 90) than during tolterodine ER treatment. Trial registration NCT02138747; registered May 13, 2014.